Design and fabrication of crankcase for single cylinder 2-strokes engine - Mohd Shukri, Mai (2007)
A crankcase is the lower part of engine which in single cylinder two-stroke engine the main function is to hold the crankshaft in parallel position and work as a vacuum medium to suck the combustion material. Mostly the crankcase is made from assembly two parts that is left side and right side. Mostly, many product of crankcase are manufactured using casting process, but in this final year project, the process in fabricate the crankcase is machining process. Here, for the final year project, the title is modeling and fabricate of crankcase for single-cylinder two-stroke engine. The process is started from designing of the crankcase by using Solid Work program. The next stage is CFD modeling and simulation by using CAM method. After that the Solid Work format is converted to Master Cam format. Here, the simulation was running before transfer to CNC milling format